Building ECCE Numerical Literacy and Science to implement fun learning - Mamah Rahmah Dewi (International Conference on Economic Business and Social Science, 2023)
The program "Building Numerical and Science Literacy in Early Childhood Education (ECCE) to Apply Fun Learning" aims to create a stimulating and fun learning environment for early childhood children. This research uses active learning approaches, contextual materials, and creativity to form a solid foundation of numerical literacy and science. With a focus on developing basic math skills and understanding science concepts, the program emphasizes the importance of parental involvement as partners in children's learning at home. Parental integration helps create continuity between school and home learning experiences, reinforcing children's positive experiences of numerical literacy and science. Regular monitoring of children's progress and continuous evaluation form the cornerstone of the program, allowing adaptation of learning approaches to suit each child's development. Flexibility in teaching methods and program adaptation are key to success, resulting in holistic literacy goals. The program not only pursues the improvement of academic skills, but also pursues positive changes in children's learning attitudes, motivation, and active participation in the learning process. As such, the program makes a significant contribution to opening the doors of numerical and science literacy from an early age, making learning a fun, inspirational, and meaningful journey for the development of ECCE children